The Relationship between Learning Motivation and Academic Procrastination in Level II Nurse Students STIKes Santa Elisabeth Medan 2021 - Lilis Novitarum; Mardiati Barus; Maria Pujiastuti; Novelia Sitompul (Jurnal Scientia, 2022)
Procrastination is a habit of delaying lecture assignments until tomorrow which is done repeatedly by students. The impact that can occur due to the behavior of delaying tasks is anxiety, anxiety, fear, regret, stress, uncontrolled emotions, panic, crying and sadness. The factor that causes academic procrastination is student learning motivation. In this study, respondents did academic procrastination. The purpose of this study was to determine the relationship between learning motivation. This research is descriptive with a cross sectional research design of 88 respondents and uses a total sampling method. The results obtained based on the level of learning motivation most have high learning motivation (95%) and based on the level of procrastination the most have moderate academic procrastination (74%). Based on the demographics of the respondents based on age, most of them have an age background of 20-24 years as much as 57.5%, based on gender the most are women as much as 89.7%, based on religion the most Christian religion is Protestant as much as 70.1% Based on ethnicity, the most Batak Toba tribe is 62.1%.